A pathological perspective to painful inguinal hernia: Report of two cases. (September 2021) - Narita, Masato; Moriyoshi, Koki; Goto, Kentaro; Yamaoka, Ryoya; Yamaguchi, Takashi
Abstract: Introduction: Preoperative inguinal pain (painful inguinal hernia) is a well-known factor associated with chronic postoperative inguinal pain (CPIP). However, it remains unclear what preventive measures should be taken in such patients. Case presentation: We report two patients with painful inguinal hernia who underwent pragmatic ilioinguinal nerve neurectomy during open anterior repair. The nerve was compressed by bulky spermatic cord lipoma in case 1 and by the hernia sac presenting over a few decades in case 2. Hematoxylin and eosin staining of the resected nerves revealed mucoid degeneration. Toluidine blue staining of resin-embedded nerve sections demonstrated that fully-myelinated axons had significantly decreased in case 1 and almost disappeared in case 2, indicating the development of massive demyelination of the ilioinguinal nerve in both cases. Discussion: In cases where the injured nerve is left in situ, CPIP may occur since demyelinating neuropathy sometimes becomes irreversible. Conclusion: Planned nerve resection via open anterior inguinal hernia repair may be an option to prevent CPIP in patients with painful inguinal hernia. Highlights: Painful inguinal hernia is a known risk factor for CPIP; however, preventive measures remains unclear. Ilioinguinal nerves were massively demyelinated in two patients with painful inguinal hernia. Severe neuropathy induced by chronic compression of the ilioinguinal nerve may be associated with painful inguinal hernia. Planned nerve resection via anterior hernia repair is an option to prevent CPIP in patients with painful inguinal hernia.